Association between organophosphate pesticide exposure and atopic dermatitis: a cross-sectional study based on NHANES 1999–2007 - Men, YueHua; Wang, YiMeng; Wu, WenTing; Chu, Ming (Frontiers in Public Health, 2025)
BackgroundOrganophosphate pesticides (OPPs) are widely used environmental chemicals with potential health impacts, but their relationship with atopic dermatitis (AD) remains unclear.MethodsUsing data from the National Health and Nutrition Examination Survey (NHANES) 1999–2007, we investigated associations between urinary OPP metabolites and AD in 4,258 adults. Six dialkyl phosphate (DAP) metabolites were measured, and weighted quantile sum (WQS) regression was used to assess mixture effects.ResultsBoth DMP (odds ratio [OR] = 1.17, 95% confidence interval [CI]: 1.05–1.31) and DMDTP (OR = 2.23, 95%CI: 1.08–4.60) showed significant positive associations with AD in fully adjusted models. WQS regression revealed significant associations between mixed OPP exposure and AD (OR = 1.25, 95%CI: 1.04–1.50), with DMP contributing most (45.8%) to the mixture effect. Stratified analyses indicated stronger associations in males, younger adults (<60 years), and smokers.ConclusionOur findings suggest that OPP exposure, particularly DMP, may be associated with increased AD risk in adults. These results provide new insights into environmental risk factors for AD.